Parameterized and automated assessment on an introductory programming course - Zampirolli, Francisco de Assis; Pisani, Paulo Henrique; Josko, João Marcelo; Kobayashi, Guiou; Fraga, Francisco; Goya, Denise; Savegnago, Heitor Rodrigues (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2020)
The generation of individualized exams can contribute to a more reliable assessment of the students. Manually performing this procedure may not be feasible, even more on a large scale. An alternative to deal with it is the automatic generation of questions. This paper discusses an innovative solution to simplify test generation and correction through parameterized questions in the context of a four-month Introduction to Programming course under a blended- learning (IP-BL) approach. It combines the open-source tool MCTest with Moodle and VPL plugin to generate and also automatically evaluate parameterized programming language questions. We applied an intervention based on this solution in two IP-BL groups (a total of 171 enrolled students) using Java.